A rational in vitro evaluation of 53 medicinal plants used in the treatment of diarrhoea and the potential use of Deinbollia oblongifolia (Sapindaceae) extracts - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.